Resource windfalls and public debt: the role of political myopia - Raveh, O; Tsur, Y (University of Oxford, 2018)
We identify an adverse consequence of natural resource windfalls, which is partic-ularly detrimental in advanced democracies. We construct a political economy modelwith endogenous public debt under exogenous resource windfall shocks, in which po-litical myopia results from reelection prospects. Reelection-seeking politicians, whilemore accountable toward their electorate, are also more myopic. The latter eectgives rise to a budget decit bias, with the ensuing debt buildup that is exacerbatedby resource windfalls. We nd that the positive eect of resource windfalls on debtincreases as the restrictions on reelection get laxer. We test the model's predictionsusing a panel of U.S. states over the period 1963-2007. Our identication strategyrests on constitutionally-entrenched dierences in gubernatorial term limits that pro-vide plausibly exogenous cross-sectional and time variation in political time horizon,and geographically-based cross-state dierences in natural endowments interacted withthe international prices of oil and gas. The empirical ndings corroborate the model'spredictions. In particular, our baseline estimates indicate that a resource windfall of$1 induces an increase of approximately g14:7 in the public debt of states with nogubernatorial term limits.